Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T12:09:47+01:00
ΔH= ΔHtw(produkty)-ΔHtw(substraty)

tlen pomijamy, wiec:
ΔHtw(sub) = ΔHtwCS₂
-1108= (-393) +2(-297) - ΔHtwCS₂
-1108=(-987) - ΔHtwCS₂
ΔHtwCS₂= 121kJ/mol

3 3 3
2010-02-01T12:29:45+01:00
Witaj

CS2 + 3 O2 = CO2 + 2 SO2 ^H = -1108 kJ/mol
^Htw.CO2 = -393 kJ/mol
^Htw.SO2 = -297 kJ/mol
^Htw. O2 = 0 kJ/mol
W oparciu o prawo Hessa jest :
^H = ^Htw.CO2 + 2*^Htw.SO2 - ^Htw.CS2 - 3*^Htw.O2 czyli
-1108 = -393 + 2( -297 ) - ^Htw.CS2 - 0 czyli
^Htw.CS2 = 1108 -393 - 594 = + 121

^Htw.CS2 = 121 kJ/mol

pozdrawiam
czarnadziura
2 3 2
2010-02-01T16:17:02+01:00
Wiedząc, że:
H CO2=-393kj/mol
H SO2=-297kj/mol

CS2 + 3O2--> CO2 + 2SO2
H=-1108kj/mol CS2


= ΔHtw(produkty)-ΔHtw(substraty)

tlen pomijamy, wiec:
ΔHtw(sub) = ΔHtwCS₂
-1108= (-393) +2(-297) - ΔHtwCS₂
-1108=(-987) - ΔHtwCS₂
ΔHtwCS₂= 121kJ/mol

2 3 2